The Battle of France 1940 - Goutard, Colonel A.; Translated by Captain A.R.P. Burgess (London Frederick Muller Ltd., 1958)
Reassessment of the fall of France in 1940. Over-all campaign plans of Germany are compared with those of France and her allies, and each battle is analyzed for its part in the fall.
Include Bibliography and Index
Keywords: World War (1939-1945) -- Military campaigns -- Western Front (World War (1939-1945)